Моделювання управління ризиками в проектах глибоководних археологічних досліджень з використанням засобів морської робототехніки - Надточий, Анатолій Вікторович (НТУ "ХПІ", 2016)
Виконано аналіз існуючих моделей управління ризиками при проведені глибоководних досліджень з використанням ненаселених підводних апаратів. На підставі виконаних досліджень розроблені моделі управління ризиками в проектах глибоководних археологічних досліджень, які пов’язані з погодними та гідрологічними умовами в районі досліджень, а також технологічним забезпеченням. Зниження вірогідних збитків в запропонованих моделях досягається шляхом мінімізації вартостей носія підводного апарату, підводного апарату та додаткового обладнання і послуг у відповідності до району та вибраної технології досліджень.

The analysis of existing risk management models at underwater works using marine robotics is conducted. Leading role of underwater remotely operated vehicle in underwater archeological research is shown. The structure of risk management model in underwater archeology projects related to weather and hydrological conditions in the investigated area is developed. The basis of the model is selection process of timing of deep archeological researches, which are favorable for meteorological and hydrological conditions and satisfy the conditions to ensure the minimum cost of the project by defining rational terms of attracting, underwater remotely operated vehicles, vessels and their crews. The structure of risk management model is developed for risks associated with technological support of underwater archaeological research. The initial data for the modelis the task to conduct archeological research, geographic coordinates and its timing. The key parameters of the model are information about characteristics of investigated artifacts, their value for classification features. The model assumes a sequence of iterative processes in pre-development of technology for underwater archaeological research, as well as determining required characteristics of robotics, support vessels and additional equipment on its basis.
Modelling of risk management in projects of deep archeological research using marine robotics funds
Keywords: підводна археологія; підводний апарат; гідрологічні умови; технологічне забезпечення; project risk management; underwater archeology